THE INFLUENCE OF WORK MOTIVATION, WORK ENVIRONMENT, AND LEADERSHIP STYLE TO PRODUCTIVITY WORK EMPLOYEE ON PTPN IV MARJANDI PLANTATION - Lisnawati; Santi Rizki; Eva Solita Pasaribu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of work motivation, work environment, and leadership style on employee work productivity at PTPN IV Kebun Marjandi. This study was motivated by the inconsistency of previous research findings regarding factors influencing work productivity and the limited research in the state-owned plantation sector. The study used a quantitative approach with an explanatory survey method. The study population was 170 permanent employees of PTPN IV Kebun Marjandi, with a sample of 119 respondents determined using the Slovin formula and simple random sampling techniques . Data were collected through a questionnaire using a five-level Likert scale. Data analysis was carried out using multiple linear regression with the help of IBM SPSS Statistics version 27, which was preceded by validity, reliability, and classical assumption tests. The results showed that work motivation, work environment, and leadership style partially and simultaneously had a positive and significant effect on employee work productivity (p < 0.05). Work motivation was the variable that had the most dominant influence on work productivity compared to other variables. The coefficient of determination value showed that variations in work productivity could be largely explained by the three independent variables in the research model. These findings confirm that increasing work productivity requires an integrated human resource management strategy through strengthening work motivation, creating a conducive work environment, and implementing an effective leadership style. This research provides an empirical contribution to the development of human resource management studies in the plantation sector and serves as a basis for company management in formulating policies for increasing work productivity sustainably.